Analysis of the Implementation of the Financial Services Authority on Data Base Protection in Online Loans - Berliano, Raden; Huzaifan, Muhammad; Gunawan, Moch. Sigit; Dimiyati, Agus (Rechtsnormen: Journal of Law, 2024)
Background. Hackers have an impact on the slowdown in economic growth, factors that affect population growth, inflation rates, and the cost of living in Indonesia. This condition has also increased demand for Online Loans as a solution to meet social needs. The inevitable technological developments in today's digital era are increasingly enriched by the emergence of Online Loan applications, which are part of information technology in the financial sector. Money lending services financial companies provide using information technology are known as online loans. Applying, approving, and disbursing funds is done online or through phone or short message (SMS) confirmation. Purpose. This study evaluates the challenges law enforcement faces in implementing the Financial Services Authority related to database protection in the online lending industry. Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analyzed using appropriate statistical methods. Results. The study results show that law enforcement against this matter still faces various significant obstacles. The two sources of online loan database leaks are consumers and financial service providers. The first factor comes from consumer behavior when making online loan transactions, providing personal data such as ID cards, phone numbers, credit card numbers, and debits. The second factor is financial service providers selling consumer data to third parties. Hackers can easily access data application systems, so ensuring the system is secure is crucial. Conclusion. The Fintech industry started online lending services in Indonesia at the end of 2014. In the following year, banks and other financial institutions also began to present a variety of loans with a fast process, which is regulated and monitored by the Financial Services Authority (OJK) under OJK Regulation Number 77/POJK.01/2016.